PREVALENCE OF WHEAT ALLERGY IN AL-KHARJ, SAUDI ARABIA - Ghonaim, Ali S. Al-; Qassam, Saad R. Al-; Kujan, Omar; Tarakji, Bassel; S, Azzegahiby; I, Azzegahiby; Wyse, Richard K.H.; Rabia, Mohammed W. Al-; Alenzi, Faris Q.B. (Journal of Ayub Medical College Abbottabad, 2013)
Background: Wheat allergy has been suggested to represent an important allergic disease. This study collates clinical and laboratory aspects in patients with wheat allergy in Al-Kharj city, Saudi Arabia. Methods: Total and specific IgE were measured in 15 suspected cases of wheat allergy. Protein allergenicity was assessed with Western blotting. Results: Significant elevation of total and specific IgE was found in 4 cases. Basophlia was also demonstrated on blood film. Western blotting results showed 2 bands (83 and 40 kDa). Conclusion: Wheat allergy must also be considered when planning treatment of asthma and eczema of adult patients. Keywords: Allergy, IgE, Asthma, Eczema, Wheat, Saudi Arabia